Potensi Chaya (Cnidoscolus aconitifolius) sebagai Sumber Sayuran Kaya Gizi bagi Masyarakat Indonesia - Indra Advent Simamora; Fitra Gustiar; Zaidan Zaidan; Irmawati Irmawati (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Simamora IA, Gustiar F, Zaidan Z, Irmawati I. 2022. Potential of chaya (Cnidoscolus aconitifolius) as a source of nutrious vegetables for Indonesian people. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 937-946. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Chaya (Cnidoscolus aconitifolius (Mill.) IM Johnst.) is an annual plant species that is not widely known by the Indonesian people. This plant has not been cultivated intensively, although Chaya is a type of vegetable plant that is rich in nutrients and has many benefits. This writing aimed to provide information on the study of the potential development of Chaya plants as a source of food, feed or as medicinal ingredients. In a tropical climate, Chaya plants have great potential to be developed as cultivated plants. This paper will examine the potential of Chaya from the aspect of agricultural cultivation and utilization of Chaya leaves. The lack of information and public knowledge regarding the nutritional content and benefits of Chaya is one of the inhibiting factors for plant development. This plant is easy to grow by propagation of stem cuttings, currently the chaya plant is still being developed on unproductive land and used as a hedge plant. With the development of information system media, it is hoped that it will increase public knowledge of the potential and benefits of Chaya leaves.